Time course of serum neuron‐specific enolase levels from infancy to early adulthood in a female patient with beta‐propeller protein‐associated neurodegeneration. Issue 5 (7th February 2023) - Hirano, Shodo; Suzuki, Yasuhiro; Ikeda, Tae; Okamoto, Nobuhiko
Abstract: Beta‐propeller protein‐associated neurodegeneration (BPAN), a subgroup of neurodegeneration with brain iron accumulation, is typically characterized by non‐progressive global developmental delay and seizures in childhood, followed by progressive neurological decline with parkinsonism and dementia in adolescence or early adulthood. It is difficult to clinically identify a patient with BPAN in childhood. Recent studies reported that serum levels of neuron‐specific enolase (NSE) were elevated in children with BPAN. We reviewed the time course of serum NSE levels in a 21‐year‐old female patient genetically diagnosed (a de novo WDR45  variant c.268A > T) with BPAN, which was suspected based on prolonged elevation of serum NSE. There was an overall tendency for serum NSE levels to decrease in a stepwise fashion. The peak serum NSE level was observed during the first 2 years of age and then decreased rapidly in 1 year. High serum NSE levels persisted between 3 and 11 years of age. Subsequently, serum NSE levels decreased and plateaued after 13 years of age. There were tendencies for both blood AST and LDH levels to decrease over time in parallel with serum NSE levels. Serum NSE levels may be a diagnostic biomarker of BPAN in children but becomes of less value in identifying a patient with BPAN after childhood.